The Relationship Between Physical Literacy and Student Participation inPhysical Education Learning - Takhwin Peryoga; Yudy Hendrayana; Reshandi Nugraha (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze the relationship between physical literacy and studentparticipation in physical education learning at MTs Daarul Fikril Uluum Binong. Aquantitative approach with a correlational research design was used. The population consisted of 166 students, from which a sample of 118 students was selectedusing the Simple Random Sampling technique, with sample size determinedthrough the Slovin formula. Data were collected using a Likert-scale questionnaireconsisting of 21 statements measuring physical literacy and 19 statements measuring student participation. The data were analyzed using descriptive statistics, theKolmogorov–Smirnov normality test, and the Pearson Product Moment correlationtest, processed with IBM SPSS Statistics version 27. The results show that bothphysical literacy and student participation fall into the Very Good category. ThePearson correlation test revealed a strong and statistically significant positive relationship between physical literacy and student participation (r = 0.790; p = 0.000;p < 0.05). These findings indicate that the higher students' physical literacy, thegreater their participation in physical education learning. Therefore, physical education teachers should give greater attention to developing students' physical literacy as an effort to increase student engagement in the learning process.